Studi Keanekaragaman dan Analisis Risiko Tumbuhan Invasif di Kawasan Taman Kelurahan Mekarmulya Kecamatan Cinambo, Kota Bandung, Provinsi Jawa Barat - Nurul Fuji Amandari; Ilvi Maulidina; Rahmat Taufik Mustahiq Akbar (Jurnal Riset Rumpun Ilmu Tanaman, 2023)
Mekarmulya Village Park, Cinambo District, Bandung City is a park in the middle of the city and industry. This area is designed to provide green open space in the midst of urban density, so it plays an important role in improving the quality of life in the environment. This research aims to conduct a diversity study and risk analysis of invasive plants in the Mekarmulya Village Park area. Sampling was carried out by roaming throughout the park area. Data processing is carried out qualitatively and is descriptive. The research results showed that the invasive plants found consisted of 11 families, 16 genera, and 16 spesies with the dominant family being the Poaceae family (25%) and the co-dominant family being the Asteraceae family (18.75%). Various habits were obtained consisting of seedlings, saplings and poles, with the largest habitus being the seedling habitus. These invasive plants have an risk on biodiversity and the ecosystem around the park.